Effect of 4‐chloro‐7‐trifluoromethyl‐10H‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid on the intraurethral pressure in a rat model of benign prostatic hyperplasia. (8th December 2015) - Choi, Bo Ram; Soni, Kiran Kumar; Zhang, Li Tao; Lee, Sung Won; So, Insuk; Kim, Hye Kyung; Park, Jong Kwan
Abstract : Objectives: To investigate the effect of 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid, a new benzofuroindole derivative, on the intraurethral pressure in a rat model of benign prostatic hyperplasia. Methods: Benign prostatic hyperplasia was induced by testosterone and 17β‐estradiol, which were administered intramuscularly once a day for 12 weeks. The effects of 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid and tamsulosin on the intraurethral pressure induced by the electrostimulation of hypogastric nerves after a single intravenous injection of 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid (10 mg/kg) or tamsulosin (10 μg/kg) were evaluated in a benign prostatic hyperplasia model. The electrostimulation‐induced intraurethral pressure was measured just before and after the injection of 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid. Bodyweight and genitourinary organ weights were recorded, and serums and tissues were subjected to hormone assays and histopathology. In addition, the expression of α1‐adrenoceptors in the prostate was measured by western blotting. Results: The benign prostatic hyperplasia groups showed increased prostatic index, increased concentrations of testosterone, free testosterone and estradiol in serum, and increased epithelial thickness of the prostate. An injection of 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid or tamsulosin significantly inhibited the elevation of electrostimulation‐induced intraurethral pressure. In addition, 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid did not cause a significant change in the blood pressure compared with tamsulosin. While the benign prostatic hyperplasia group showed increased the expression of α1‐adrenoceptors, the 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid or tamsulosin injection into a rat model of benign prostatic hyperplasia decreased the expression of α1‐adrenoceptors. Conclusions: These findings show that 4‐chloro‐7‐trifluoromethyl‐10 H ‐benzo[4, 5]furo[3, 2‐b]indole‐1‐carboxylic acid might be beneficial for lowering the intraurethral pressure associated with benign prostatic hyperplasia, and it could represent a therapeutic option for benign prostatic hyperplasia patients.